2010
DOI: 10.1016/j.bpj.2010.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Role of Actin Depolymerization in the Regulation of Cochlear Outer Hair Cell Motility

Abstract: Cochlear outer hair cells undergo reversible changes in shape when externally stimulated. This response, known as OHC motility, is a central component of the cochlear amplifier, the mechanism responsible for the high sensitivity of mammalian hearing. We report that actin depolymerization, as regulated by activation/inhibition of LIMK/cofilin-mediated pathways, has a pivotal role in OHC motility. LIMK-mediated cofilin phosphorylation, which inhibits the actin depolymerizing activity of this protein, increases b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…In relation to this point Kalinec and his co-workers (Matsumoto et al, 2010) concluded that actin depolymerization, as regulated by activation/inhibition of LIMK/cofilin-mediated pathways, strongly supported the hypothesis that the cytoskeleton has a major role in the regulation of OHC motility, with actin depolymerization having a pivotal role in modulating cochlear amplification. Matsumoto et al discovered that both electromotile amplitude and total length of OHCs was increased by LIMK-mediated cofilin phosphorylation, but OHC electromotile amplitude and OHC length were decreased when cofilin phosphorylation was reduced.…”
Section: The "Slow"effectmentioning
confidence: 77%
“…In relation to this point Kalinec and his co-workers (Matsumoto et al, 2010) concluded that actin depolymerization, as regulated by activation/inhibition of LIMK/cofilin-mediated pathways, strongly supported the hypothesis that the cytoskeleton has a major role in the regulation of OHC motility, with actin depolymerization having a pivotal role in modulating cochlear amplification. Matsumoto et al discovered that both electromotile amplitude and total length of OHCs was increased by LIMK-mediated cofilin phosphorylation, but OHC electromotile amplitude and OHC length were decreased when cofilin phosphorylation was reduced.…”
Section: The "Slow"effectmentioning
confidence: 77%
“…In the cochlea, hair cells are arranged in a single row of inner hair cells (IHCs) and three rows of outer hair cells (OHCs). Although IHCs and OHCs are believed to share common mechanotransduction machinery, they have distinct roles during sound detection: IHCs are true sensors, whereas OHCs function as an amplifier through an active process that involves stereociliary and somatic motility (Matsumoto et al, 2010;Schwander et al, 2010). Stereocilia, which are actin-based protrusions, are known as exquisitely organized microvilli and filopodia composed of hundreds of parallel actin filaments with the plus ends at the distal tip; however, stereocilia are organized into precise rows of graded height (Frolenkov et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Cdc42 is essential for filopodia formation (Chen et al, 2000;Yang et al, 2006), whereas Rac and RhoA induce lamellipodia and stress fiber formation, respectively (Heasman and Ridley, 2008). Cdc42 induces actin polymerization through its interaction with actin nucleators (Campellone and Welch, 2010), including the Arp2/3 complex component N-WASP (Takenawa and Suetsugu, 2007), and promotes filopodia induction and stabilization through the PAK/LIM kinase (LIMK) pathway and the cofilin phosphorylation cycle (Matsumoto et al, 2010;Melendez et al, 2011). Cdc42 also regulates AJC formation in vitro (Otani et al, 2006;Qin et al, 2010) and in vivo (Melendez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Rac may participate in cell adhesion, proliferation, and movements during otic development [11], [12]. Several studies have suggested that the activation/inhibition of Rho pathways control the actin depolymerization rate in the outer hair cells [13], [14]. Although best known for their roles in the regulation of membrane traffic, there is growing evidence that GTPases in the Arf family can also act via changes in actin.…”
Section: Introductionmentioning
confidence: 99%